2001
DOI: 10.1038/sj.mp.4000900
|View full text |Cite
|
Sign up to set email alerts
|

D10S1423 identifies a susceptibility locus for Alzheimer's disease in a prospective, longitudinal, double-blind study of asymptomatic individuals

Abstract: Typical, later-onset forms of Alzheimer's disease (AD) appear to be influenced by multiple susceptibility loci, combinations of which contribute to the development of this disorder. We previously reported the results of a systematic survey of the human genome for the identification of highly informative DNA polymorphisms (SSTRPs) that target new AD risk genes. In addition to the APOE locus, our survey detected five new candidate susceptibility loci for AD, including D10S1423. An association of the D10S1423 234… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 61 publications
(51 reference statements)
1
25
0
Order By: Relevance
“…The effect of a second susceptibility gene (in this case, the MAOA gene) may become apparent, however, when gene-gene interactions with other genes are analysed. 24,25 We have illustrated the effectiveness of this approach in our gene-gene interaction analysis, and have also shown how the relationship of the associated susceptibility loci (in this case the MAOA-uVNTR and NETpPR) may be easily characterised in a contingency table.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a second susceptibility gene (in this case, the MAOA gene) may become apparent, however, when gene-gene interactions with other genes are analysed. 24,25 We have illustrated the effectiveness of this approach in our gene-gene interaction analysis, and have also shown how the relationship of the associated susceptibility loci (in this case the MAOA-uVNTR and NETpPR) may be easily characterised in a contingency table.…”
Section: Discussionmentioning
confidence: 99%
“…33 The efficiency of this association study was enhanced by genotyping pools of DNA from 100 adults with RE-MDD and 100 adult controls who had no personal or family history of mental disorders. This case-control strategy for identifying genetic determinants that contribute to the expression of complex, non-Mendelian human disorders, which we have also previously employed to identify susceptibility loci for Alzheimer's disease, [34][35][36][37][38][39][40] is receiving growing support in the human genetics community. 41 In our previous investigation, allelic associations with RE-MDD were observed for 19 of the 387 SSTRPs employed in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…10 Furthermore, the experiment-wide significance levels in at least two of the positive studies were only marginal, 1,3 and the association was only evident when controlling for the presence of APOE e4 in the third study. 2 Finally, the fourth analysis, with the greatest number of cases, failed to replicate these findings altogether. 4 Of note, several research groups using varying samples and various methods of linkage and/or association analysis [5][6][7][8]11 have implicated chromosome 10 as harboring a novel AD locus.…”
mentioning
confidence: 72%
“…SIR -Recently, three studies reported genetic association of an anonymous microsatellite marker on chromosome 10p12 (D10S1423) and Alzheimer's disease (AD), [1][2][3] whereas a fourth study failed to replicate these findings 4 . At least four linkage studies have implicated regions on chromosome 10 as likely to harbor an AD susceptibility gene [5][6][7][8] ; however, all reported linkage peaks map considerably distal to D10S1423 (440 cM).…”
mentioning
confidence: 82%